2017
DOI: 10.1037/pro0000095
|View full text |Cite
|
Sign up to set email alerts
|

A mixed-method study of psychologists’ use of multicultural assessment.

Abstract: Despite practice guidelines and ethical standards that provide imperatives for clinicians to utilize multicultural assessment (MCA), little is known about how the average psychologist actually conducts MCA. The current mixed-method study was designed to investigate clinicians' training and use of MCA practice strategies. Participants were 239 (107 male, 131 female, 1 other gender) licensed psychologists residing in the United States and Canada who were recruited from the American Psychological Association prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…3 If more in-depth cultural assessment is needed, what is the role of alternative cultural assessments? Can the core CFI be used as a screening evaluation, to be expanded not only by employing the CFI supplementary modules, but additionally or alternatively by longer cultural assessments, such as the Brief Cultural Interview (Groen, Richters, Laban, & Devillé, 2017), the Cultural Interview (Rohlof, Groen, van Dijk, & Knipscheer, 2017), the Bloomsbury Cultural Formulation Interview (Jadhav, 2013), 4 the McGill Illness Narrative Interview (Groleau, Young, & Kirmayer, 2006), or other approaches (Edwards et al., 2017)?…”
Section: Identifying Effective Dissemination and Implementation Stratmentioning
confidence: 99%
See 1 more Smart Citation
“…3 If more in-depth cultural assessment is needed, what is the role of alternative cultural assessments? Can the core CFI be used as a screening evaluation, to be expanded not only by employing the CFI supplementary modules, but additionally or alternatively by longer cultural assessments, such as the Brief Cultural Interview (Groen, Richters, Laban, & Devillé, 2017), the Cultural Interview (Rohlof, Groen, van Dijk, & Knipscheer, 2017), the Bloomsbury Cultural Formulation Interview (Jadhav, 2013), 4 the McGill Illness Narrative Interview (Groleau, Young, & Kirmayer, 2006), or other approaches (Edwards et al., 2017)?…”
Section: Identifying Effective Dissemination and Implementation Stratmentioning
confidence: 99%
“…Many clinical training programs have incorporated the CFI in teaching cultural competence (e.g., Díaz, Armah, Linse, Fiskin, Jordan, & Hafler, 2016; Mills et al., 2016) and the CFI is often included in grant rounds and continuing education programs for practicing clinicians. This level of acceptance likely has occurred because the CFI meets a need in the field for a brief, skills-based, teachable method of carrying out cultural assessment with individual patients (Edwards, Burkard, Adams, & Newcomb, 2017). Evidence so far holds promise for the wide applicability of the CFI; for example, several independent studies have shown that clinicians, patients, and family members find it feasible and acceptable, and that they expect it would be useful to care provision (Lewis-Fernández et al., 2017; Paralikar et al., 2015; Skammeritz, Lindberg, Mortensen, Norredam & Carlsson, 2020; Wallin, Dahlin, Nevonen, & Bäärnhielm, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A number of ethical and practice guidelines and standards providing recommendations for assessment practices with culturally diverse populations have been put forth (American Educational Research Association, American Psychological Association [APA], & National Council on Measurement in Education, 2014;APA, 2003APA, , 2017Clauss-Ehlers, Chiriboga, Hunter, & Roysircar, 2019; see also Suzuki & Ponterotto, 2008;Uzzell, Ponton, Ardila, 2007) and the professional and ethical obligation to develop competency in cross-cultural assessment, including consideration of cultural and sociodemographic factors and use of appropriate norms, has been widely discussed in the literature (Boone, Victor, Wen, Razani, & Pontón, 2007;Brickman, Cabo, & Manly, 2006;Judd et al, 2009;Rivera Mindt, Byrd, Saez, & Manly, 2010). Despite this, a recent study found that almost 40% of psychologists surveyed do not use any multicultural assessment theories or frameworks in their assessments, and many clinicians omit basic strategies such as consulting the literature on a client's cultural background (Edwards, Burkard, Adams, & Newcomb, 2017). Further, a survey of neuropsychologists who provide services to Hispanic populations found that most are not adequately prepared and lack the appropriate tools to work with this population (Echemendia & Harris, 2004;Echemendia, Harris, Congett, Diaz, & Puente, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…First, education and supervision appear to be a significant factor. Edwards et al (2017) found that younger clinicians tend to incorporate more multicultural assessment approaches in their work, which they suggest is likely a function of changing accreditation standards. Another barrier may simply be a scarcity of assessment resources to put cross-cultural information to meaningful use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation